(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Vasomotor and allergic rhinitis are common upper airway conditions that significantly affect patients’ quality of life and impose a substantial socio-economic burden. This article provides a comprehensive overview of their modern treatment strategies, based on current international guidelines. The pathogenesis, diagnostic approaches, and therapeutic options—ranging from pharmacotherapy (antihistamines, corticosteroids, antileukotrienes) to biologics and surgical methods—are thoroughly discussed. Emphasis is placed on the integration of innovative treatments such as specific immunotherapy, botulinum toxin injections, and minimally invasive surgical techniques. The review highlights evidence-based recommendations from leading organizations such as EAACI and ARIA, aiming to optimize patient outcomes through a personalized and multidisciplinary approach.